Bimodal miniature and evoked end-plate potentials in adult mouse neuromuscular junctions. - Kelly, S S (1984)
Intracellular recordings of spontaneous miniature end-plate potentials (m.e.p.p.s) in muscles from adult CBF-1 mice revealed a population of muscle fibres in which the amplitude distribution of m.e.p.p.s was bimodal. The large mode m.e.p.p.s were similar to those from fibres having unimodal amplitude distributions and the small mode m.e.p.p.s were about one-half to one-quarter the amplitude of the large mode. In five diverse muscle groups (extensor digitorum communis, gluteus maximus, diaphragm, extensor digitorum longus, and soleus) from mice 10-12 or 31 months of age, bimodal m.e.p.p. amplitude distributions were present in about 20% of fibres sampled. In the common bimodal distribution (type 1), the rise times of small mode m.e.p.p.s were similar to those of large mode m.e.p.p.s. A rare class of small mode m.e.p.p.s (type 2) having long rise times was also observed. Amplitudes and half-decay times of type 1 small mode m.e.p.p.s increased in the presence of an anticholinesterase (edrophonium). Increasing extracellular potassium concentration led to an increase in large mode m.e.p.p. frequency but had more variable effects on small mode frequency. In the few cases available for study, type 2 small mode m.e.p.p.s disappeared after addition of edrophonium or increased potassium. When the extracellular calcium/magnesium ratio was reduced, large mode but not small mode m.e.p.p. frequency decreased. In almost all muscle fibres in which end-plate potentials (e.p.p.s) were evoked by nerve stimulation at 20 Hz in low calcium/high magnesium solution, small mode e.p.p.s similar to small mode m.e.p.p.s appeared during 'failures' of large mode m.e.p.p.s. Also, in twelve out of fifteen fibres which had unimodal m.e.p.p. amplitude distributions, small mode e.p.p.s appeared which were similar in amplitude to small mode m.e.p.p.s in fibres with type 1 bimodal m.e.p.p.s. Thus, if both spontaneous and evoked potentials are included, small mode m.e.p.p.s are present at most CBF-1 mouse adult neuromuscular junctions independent of muscle type or animal age. Small and large mode m.e.p.p.s differ in certain responses but both are evoked by nerve stimulation at physiological frequencies and therefore participate in normal neuromuscular synaptic activity. The possible origin of small mode m.e.p.p.s is discussed.